Production of Gunpowder and Ammunition as a “Bottleneck” of the Soviet Military Economy and Its Impact on Armed Struggle in 1941–1945 - Alexey Isaev (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
The article is devoted to the problem of gunpowder production in the USSR and the emergence of a “bottleneck” in the production of ammunition in the period preceding the Great Patriotic War and the development of the situation during the war. Even before the loss of enterprises in the European part of the country, the situation was unfavorable; the subsequent loss of capacity and evacuation only worsened the situation. The thesis is postulated about an insufficient raw material base for alcohol, the main pyroxylin gunpowders for the USSR at the beginning of the war, with the underdevelopment of the production of ballistite (nitroglycerin) gunpowder in the country. The shortage of ballistite gunpowder restrained the use of the latest artillery systems of the Red Army, adopted for service in 1938–1939, and the introduction of rocket artillery. The process of the introduction and expansion of the production of new types of gunpowder, the technological breakthrough achieved in 1942 thanks to the work of engineer and scientist A.S. Bakayev, and the ensuring of a sharp increase in the production of ballistite gunpowder are analyzed. The article examines the provision of the armed forces with ammunition and the military construction measures taken by the military command bodies to solve the problem of gunpowder shortage. The problem required the transformation of the organizational and staff structure of the formations with an emphasis on mortars of various calibers. Mortar rounds required a smaller charge of gunpowder compared to barrel artillery, which made it possible to provide satisfactory fire damage to the enemy with smaller volumes of its production in the country as a whole. A comparative analysis of the ammunition consumption by the Wehrmacht and the Red Army during the war is carried out, taking into account the nomenclature of rounds. Statistical data show that the Wehrmacht maintained a long-term advantage in the consumption of heavy artillery ammunition. Such an advantage negatively affected the course of hostilities, the ability of Soviet troops to destroy enemy fortifications, and the Wehrmacht’s successful reliance on artillery. In turn, the Red Army consistently had an advantage in the number of mortar rounds spent, including large-caliber 120 mm, which was uncharacteristic for the Wehrmacht. The article concludes that the preconditions for the ammunition supply crisis that arose before 1941 and the role of innovations in stabilizing the situation with the supply of ammunition to the armed forces.